A Ternary Solvent Method for Large‐Sized Two‐Dimensional Perovskites. Issue 9 (18th January 2017) - Chen, Junnian; Gan, Lin; Zhuge, Fuwei; Li, Huiqiao; Song, Jizhong; Zeng, Haibo; Zhai, Tianyou
Abstract: Recent reports demonstrate that a two‐dimensional (2D) structural characteristic can endow perovskites with both remarkable photoelectric conversion efficiency and high stability, but the synthesis of ultrathin 2D perovskites with large sizes by facile solution methods is still a challenge. Reported herein is the controlled growth of 2D (C4 H9 NH3 )2 PbBr4 perovskites by a chlorobenzene‐dimethylformide‐acetonitrile ternary solvent method. The critical factors, including solvent volume ratio, crystallization temperature, and solvent polarity on the growth dynamics were systematically studied. Under optimum reaction condition, 2D (C4 H9 NH3 )2 PbBr4 perovskites, with the largest lateral dimension of up to 40 μm and smallest thickness down to a few nanometers, were fabricated. Furthermore, various iodine doped 2D (C4 H9 NH3 )2 PbBr x I4− x perovskites were accessed to tune the optical properties rationally. Abstract : Star‐crossed : Ultrathin and large two‐dimensional (C4 H9 NH3 )2 PbX4 perovskites were synthesized by a ternary solvent method. The critical factors, including temperature, solvent volume ratio, and solvent types, that affect the growth dynamics were studied. ACN=acetonitrile, CB=chlorobenzene, DMF= N, N ‐dimethylformamide.